Linguistic foodscape as conveyed through online food menus - Lim, Chia Wei (2017)
This research focuses on the current concern of language use in a particular environment which is encapsulated broadly as linguistic landscape. The study provides insights into language use in a narrowed context which will articulate social realities in relation to linguistic “foodscape” with a Malaysian flavour. It examines explores textual and non- textual linguistics in the form of online food menus. For this study, an internet search was conducted to identify online food menus identified by referred to all eatery shops in the largest shopping mall in Klang Valley. The search yielded online menus only from 37 shops. The menus were then studied in detail both for their linguistic expressions related to cuisinary language and their accompanying non-linguistic expressions. Next, the study explore how different cultures affect the Malaysian linguistic foodscape. The final part of the study discusses linguistics features pertaining to foods that contribute to the linguistic foodscape. The findings show that English is the most widespread language used in the Malaysian foodscape as found in the online food menus. The findings also showcase the interrelations between the patterns of language and script use, and non-linguistic expressions which together convey a distinct Malaysian cultural identity related to food menus. This study adds information to a vibrant area of social language use which has deep implications for practices in human food consumption. They could also reflect sustainability in food economies and market trends which are important aspects in economic and national development. In sum, the study touches on social and cultural capital contextualized within sets of personal values which make language use unique and dynamic.